Denotation and Connotation of Male Emotional Devotion in Sam Smith’s in The Lonely Hour Album - Arsyi Azwar Ibadurokhman; Yuyun Nurulaen; R. Myrna Nur Sakinah (Interling : International Journal of English Language Teaching, Literature and Linguistics, 2026)
The representation of male emotional devotion in popular song lyrics has received limited scholarly attention, particularly from a semiotic perspective that examines how emotional meanings are constructed through interconnected songs within a single album. Therefore, this study aims to analyze the denotative and connotative meanings that construct the representation of male emotional devotion in Sam Smith’s In the Lonely Hour album. This study employed a qualitative descriptive method using Roland Barthes’ semiotic theory. The data consisted of six lyric excerpts selected from three songs in Sam Smith’s In the Lonely Hour album, namely Stay With Me, Lay Me Down, and I’m Not the Only One. The data were collected from the official lyrics available on Spotify and analyzed through Barthes’ concepts of denotation and connotation. The findings reveal that the denotative meanings portray emotional experiences commonly found in romantic relationships, while the connotative meanings construct male emotional devotion through emotional vulnerability, longing, loyalty, and perseverance despite emotional hardship. Collectively, the selected lyrics represent male emotional devotion as a progressive emotional journey rather than a single emotional condition. This study contributes to semiotic studies by demonstrating how interconnected songs within one album collectively construct a coherent representation of male emotional devotion.